(x2-y2-z2) p+2xyz=2xz
Given equation is Lagrange's linear equation "Pp+Qq=R"
The auxiliary equation is: "\\frac{dx}{x^2-y^2-z^2}=\\frac{dy}{2xy}=\\frac{dz}{2xz}"
Taking two last ratios:
"\\frac{dy}{2xy}=\\frac{dz}{2xz} \\implies \\frac{dy}{y}=\\frac{dz}{z}"
Integrating "\\ln{y}=\\ln{z}+\\ln{a} \\implies y=az"
Taking Lagrangian multipliers as, x,y,z, each ratios of "\\frac{dx}{x^2-y^2-z^2}=\\frac{dy}{2xy}=\\frac{dz}{2xz}"
"=\\frac{xdx+yd{y}+zdz}{x(x^2-y^2-z^2)+2xy^2+2xz^2}=\\frac{xdx+yd{y}+zdz}{x(x^2+y^2+z^2)}"
Now take,
"\\frac{dy}{2xy}=\\frac{xdx+ydy+zdz}{x(x^2+y^2+z^2)} \\implies \\frac{dy}{y}=\\frac{d(x^2+y^2+z^2)}{(x^2+y^2+z^2)}" "\\implies \\log{y}=\\log{x^2+y^2+z^2}" "\\implies y=x^2+y^2+z^2"
"f(\\frac{y}{z},\\frac{x^2+y^2+z^2}{y})=0"
Comments
Leave a comment